Caffeine versus aminophylline for the prevention of apnoea of prematurity in a teaching hospital in South Africa - Natalie Schellack; Andries G.S. Gous; Patience B. Mawela (South African Family Practice)
Study objectives: To determine the safety and efficacy of the use of oral anhydrous caffeine and intravenous aminophylline in the neonatal population using therapeutic drug levels and clinical effects as markers for determination.